2014
DOI: 10.3171/2014.8.focus14449
|View full text |Cite
|
Sign up to set email alerts
|

A socioeconomic analysis of intraoperative neurophysiological monitoring during spine surgery: national use, regional variation, and patient outcomes

Abstract: Object In the United States in recent years, a dramatic increase in the use of intraoperative neurophysiological monitoring (IONM) during spine surgeries has been suspected. Myriad reasons have been proposed, but no clear evidence confirming this trend has been available. In this study, the authors investigated the use of IONM during spine surgery, identified patterns of geographic variation, and analyzed the value of IONM for spine surgery cases. Methods In this retrospective analysis, the Nationwide Inpatie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 20 publications
1
27
2
1
Order By: Relevance
“…11,17,9,35,36 Furthermore, we found that corpectomies may be higher risk with a neurological injury rate of 1.02%.…”
Section: Discussionmentioning
confidence: 60%
“…11,17,9,35,36 Furthermore, we found that corpectomies may be higher risk with a neurological injury rate of 1.02%.…”
Section: Discussionmentioning
confidence: 60%
“…The intuitive reason for the utility of ION is to raise warning against devastating neurologic complications that can be prevented with intervention, such as reducing the degree of distraction, adjusting retractors, removing hardware, and minimizing the length of surgery. 13 In a retrospective study of 443 194 patients by James et al, 14 the utilization of ION within the United States increased from 1% of all spine procedures in 2007 to 12% in 2011, which are lower than the 37.6% overall utilization rate in scoliosis surgery found in this study. This difference can be accounted for by the inclusion of a wide range of spinal procedures including microdiscectomy in the study by James et al 14 These procedures traditionally do not utilize ION to the same degree as scoliosis surgery.…”
Section: Discussionmentioning
confidence: 55%
“…13 In a retrospective study of 443 194 patients by James et al, 14 the utilization of ION within the United States increased from 1% of all spine procedures in 2007 to 12% in 2011, which are lower than the 37.6% overall utilization rate in scoliosis surgery found in this study. This difference can be accounted for by the inclusion of a wide range of spinal procedures including microdiscectomy in the study by James et al 14 These procedures traditionally do not utilize ION to the same degree as scoliosis surgery. Furthermore, studies have shown no clear benefit or even recommendation against ION in certain low-risk spinal procedures.…”
Section: Discussionmentioning
confidence: 55%
“…Contrary to our results, they reported a steady increase in neuromonitoring rates for lumbar procedures from 0.6% to 12.6% from 2007 to 2011, and showed regional differences in neuromonitoring usage. 22 However, their inclusion criteria was not selective and included all lumbar procedures (including fusion and non-fusion surgeries), and also included all forms of ION (not just limited to EMG). Additionally, their data included 15% non-elective cases, a subset of patients that were excluded from our dataset.…”
Section: Discussionmentioning
confidence: 99%